Dynamics of the Size Distribution of the Russian Non-Capital Cities in the Post-Soviet Period - Bufetova, Anna N. (Economy of Regions, 2020)
The urban system and its diversity are essential resources for economic development. At the intra-regional level, cities that do not have the status of the regional administrative centre shape the structure and diversity of the urban system. The article presents the results of the study on the distribution of non-capital Russian cities (depending on their size) as well as on the mobility patterns that influence their dynamics in the post-Soviet period. Based on data about the population of the Russian cities in the period 1991 — 2016, the study uses the method for analysing the dynamics of the distribution with the application of Markov chains. The study has demonstrated the predominance of downward mobility of non-capital cities within the city size distribution, which results in their considerable concentration at the left side of the distribution and the decrease in the diversity of city size. Simultaneously, the mobility of cities is more intense in the eastern part of the country, as the mobility patterns contribute to the preservation of greater diversity of city size (compared to the western part). It is possible to identify three groups of non-capital cities that differ in mobility patterns and distribution directions. The first group includes cities belonging to agglomerations of large regional capitals, whose dynamics of distribution are opposite to the dynamics of the distribution of the totality of non-capital cities. The second group comprises cities belonging to the agglomeration shadow with the most unfavourable dynamics of the distribution. The third group contains remote cities located in the periphery, which show a slight tendency towards the formation of a bimodal distribution. The scale of these groups differs in the eastern and western parts of Russia. The findings complement the results of other studies, expand knowledge about the modern dynamics of regional settlement systems, as well as determine further research areas. The revealed negative trends in the evolution of the city size distribution substantiate the need for a transition to the regulated development of the urban system. Such an approach should consider the consequences of the spatial development policy for different groups of cities and should strive to maintain the diversity of settlement systems.